Effects of the ACE2-Ang-(1-7)-Mas axis on gut flora diversity and intestinal metabolites in SuHx mice - Abudukeremu, Asimuguli; Aikemu, Ainiwaer; Yang, Tao; Fang, Lei; Aihemaitituoheti, Adilai; Zhang, Yupeng; Shanahaiti, Daliya; Nijiati, Yiliyaer (Frontiers in Microbiology, 2024)
Objective Pulmonary artery hypertension (PAH) poses a significant challenge due to its limited therapeutic options and high mortality rates. The ACE2-Ang-(1-7)-Mas axis plays a pivotal role in regulating blood pressure and inhibiting myocardial remodeling. However, the precise mechanistic links between the ACE2-Ang-(1-7)-Mas axis and PAH remain poorly understood. This study aimed to elucidate the involvement of the ACE2-Ang-(1-7)-Mas axis in the development of PAH. Methods PAH was induced in mice using Sugen5416/hypoxia, PAAT/PET ratio and PA were detected using cardiac ultrasound; inflammation related factors such as MCP-1, TNF, IL-10and IL-12p70 were detected in intestines using cytometric bead array (CBA) kits; histopathological and morphological changes in lung and intestinal tissues were assessed via HE staining and Masson staining to evaluate the progression of PAH. Immunohistochemistry and western blotting were employed to determine the expression levels of two tight junction proteins, occludin and ZO-1, in intestinal tissues. Additionally, 16rRNA sequencing and non-targeted metabolomics by LC-MS/MS techniques were utilized to investigate the impact of the ACE2-Ang-(1-7)-Mas axis on microbial diversity and metabolomics of intestinal contents. Results Activation of the ACE2-Ang-(1-7)-Mas axis improves heart function, reduces intestines inflammatory factors and ameliorates pathological and histological alterations in SuHx mice. This activation notably upregulated the expression of occludin and ZO-1 proteins in intestinal tissues and promoted the proliferation of SCFA-producing bacteria genera, such as g_Candidatus_Saccharimonas. Furthermore, it enhanced the abundance of beneficial metabolites, including tryptophan and butyric acid. Conclusion The findings suggest that modulation of the ACE2-Ang-(1-7)-Mas axis can alleviate PAH by regulating intestinal microbes and metabolites. These results highlight the potential of the ACE2-Ang-(1-7)-Mas axis as a promising therapeutic target for clinical management of PAH.